Resin composition, dry film, cured product, and light-emitting element-mounting substrate
Through the resin composition of specific components, the product defect problem of white pad resistors when increasing reflectivity is solved, and a white pad resistor with high reflectivity and is not prone to defects is achieved, which improves the reliability and processing performance of the product.
Patent Information
- Application Number
- JP2023187237
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2023-10-31
- Publication Date
- 2025-02-05
- Estimated Expiration
- 2043-10-31
AI Technical Summary
Existing white pad resistors are prone to product defects and it is difficult to ensure product quality while improving reflectivity.
A resin composition containing cyclohexyl methacrylate, a carboxyl group-containing alkali-soluble polymer, a urethane-containing polymer and titanium dioxide is used to form a white pad resistor with high reflectivity and no defects occurring by controlling the proportion of each component and the reaction conditions.
A high reflectivity white pad resistor is achieved, reducing the occurrence of product defects and improving product reliability and processing performance.
Smart Images

Figure 0007627321000002 
Figure 0007627321000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a resin composition, a dry film, a cured product, and a light-emitting element-mounting substrate. [Background technology]
[0002] White solder resist is sometimes used for displays. By using white solder resist, it not only functions as a permanent protective film for circuits, which is required of normal solder resist, but also increases the reflectance when LEDs and other devices are mounted, making it possible to increase brightness.
[0003] For example, Patent Document 1 discloses a technique for producing a white solder resist using a resin composition that contains cyclohexyl methacrylate as a copolymer raw material and also contains titanium oxide or the like. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Japanese Patent Application Publication No. 11-087927 Summary of the Invention [Problem to be solved by the invention]
[0005] However, it has been found that when attempting to achieve a high reflectance with the white solder resist according to the conventional technology, defective products are likely to occur.
[0006] Therefore, an object of the present invention is to provide a resin composition that can be used to produce a white solder resist that has high reflectance and is less likely to produce defective products. [Means for solving the problem]
[0007] The present inventors have found that the above problems can be solved by combining specific components, and have completed the present invention.
[0008] One aspect of the present invention is a resin composition. The resin composition contains an alkali-soluble polymer (A) containing a cyclohexyl group and a carboxyl group, a urethane polymer (B), a compound (C) containing a thiol group, and a white pigment (D).
[0009] The white pigment (D) preferably contains titanium oxide. The urethane polymer (B) preferably contains a carboxyl group. When the total amount of the alkali-soluble polymer (A), the urethane polymer (B) and the compound (C) is taken as 100 parts by mass, the content of the white pigment (D) is preferably 200 to 500 parts by mass in terms of solid content. The resin composition preferably contains a polymerization initiator.
[0010] Another embodiment of the present invention is a dry film obtained by applying the resin composition onto a first film.
[0011] Yet another embodiment of the present invention is a cured product obtained by using the resin composition or the dry film.
[0012] Yet another aspect of the present invention is a light-emitting element mounting substrate having the cured product. Effect of the Invention
[0013] According to the present invention, there is provided a resin composition capable of producing a white solder resist having high reflectance and hardly producing defective products. [Brief description of the drawings]
[0014] [Figure 1] FIG. 1 is a conceptual top view of a portion of a light-emitting element mounting substrate. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] In the present specification, when isomers exist in the compounds described, all possible isomers can be used in the present invention, unless otherwise specified.
[0016] In this specification, when the upper limit and the lower limit of a numerical range are separately described, all combinations of the lower limit and the upper limit are substantially described, provided that there is no contradiction.
[0017] In this specification, unless otherwise specified, various measurements are performed at room temperature (25° C.).
[0018] In this specification, the number average molecular weight and weight average molecular weight are values measured by gel permeation chromatography (GPC) and converted using a calibration curve prepared using standard polystyrene.
[0019] In this specification, there may be cases where the components contained in the resin composition and the components contained in the resin layer or the like which is a dried coating film of the resin composition are described without distinction.
[0020] In this specification, "(meth)acrylic" is meant to include both "acrylic" and "methacrylic", and "(meth)acrylate" is meant to include both "acrylate" and "methacrylate".
[0021] In this specification, the acid value is determined by dissolving a sample in a titration solvent consisting of a 1:1 mixture of xylene and dimethylformamide by mass, titrating the sample with a 0.1 mol / L potassium hydroxide-ethanol solution by potentiometric titration, and calculating the amount of potassium hydroxide solution titrated up to the endpoint, with the inflection point on the titration curve being the endpoint.
[0022] The components and methods / applications of use of the resin composition according to the present disclosure will be described below.
[0023] <<<Components of resin composition>>> The resin composition according to the present disclosure preferably contains an alkali-soluble polymer (A) containing a cyclohexyl group and a carboxyl group, a urethane polymer (B), a compound (C) containing a thiol group (hereinafter referred to as thiol group-containing compound (C)), and a white pigment (D). The resin composition according to the present disclosure preferably contains a thermosetting resin (E). The resin composition according to the present disclosure preferably contains a polymerization initiator (F). The resin composition according to the present disclosure may contain another component (G). Each component will be described below.
[0024] <<Alkali-soluble polymer (A)>> The alkali-soluble polymer (A) is not particularly limited as long as it is a polymer containing a cyclohexyl group and a carboxyl group.
[0025] Examples of the alkali-soluble polymer (A) include a copolymer of a monomer containing a cyclohexyl group and a monomer containing a carboxyl group, a modified product in which the terminal portion of a polymer having a cyclohexyl group is substituted with a carboxyl group-containing functional group, a modified product in which the terminal portion of a polymer having a carboxyl group is substituted with a cyclohexyl group-containing functional group, etc. The alkali-soluble polymer (A) is preferably a copolymer of a monomer containing a cyclohexyl group and a monomer containing a carboxyl group.
[0026] The monomer having a cyclohexyl group is not particularly limited, and examples thereof include compounds containing a cyclohexyl group and a (meth)acryloyl group, such as cyclohexyl (meth)acrylate, 1,4-cyclohexanedimethanol mono(meth)acrylate, and 3,4-epoxycyclohexyl (meth)acrylate.
[0027] The monomer containing a carboxyl group is not particularly limited, and examples thereof include compounds containing a carboxyl group and a (meth)acryloyl group, such as (meth)acrylic acid, carboxyethyl (meth)acrylate, mono(2-(meth)acryloyloxyethyl) succinate, and monohydroxyethyl (meth)acrylate phthalate.
[0028] By copolymerizing these monomers under conventionally known conditions, an alkali-soluble polymer (A) can be produced. The ratio of the monomer having a cyclohexyl group to the monomer having a carboxyl group can be any ratio, but a ratio of 30:70 to 70:30 on a mass basis is preferred in terms of resolution and reflectance.
[0029] In this case, the monomers used in copolymerizing the alkali-soluble polymer (A) may contain monomers (other monomers) other than the monomer having a cyclohexyl group and the monomer containing a carboxyl group.
[0030] The other monomers are not particularly limited. Examples of the other monomers include (meth)acrylates that do not have a cyclohexyl group, such as methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, hexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, stearyl (meth)acrylate, isobornyl (meth)acrylate, lauryl (meth)acrylate, 2-methylbutyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, and 2-hydroxypropyl (meth)acrylate.
[0031] The ratio of the other monomers to the total monomers constituting the alkali-soluble polymer (A) is, for example, 50 mol % or less, 30 mol % or less, 25 mol % or less, or 20 mol % or less. The lower limit of the ratio of the other monomers is, for example, 1 mol %, 2 mol %, 5 mol %, or 10 mol %.
[0032] The alkali-soluble polymer (A) preferably has an ethylenically unsaturated group (a hydrocarbon group having an unsaturated double bond). The ethylenically unsaturated group is preferably a (meth)acryloyl group.
[0033] The alkali-soluble polymer (A) having an ethylenically unsaturated group can be produced, for example, by adding a compound having one epoxy group and one or more ethylenically unsaturated groups (preferably (meth)acryloyl groups) in the molecule, such as glycidyl (meth)acrylate, α-methylglycidyl (meth)acrylate, etc., to a copolymer of a monomer having a cyclohexyl group and a monomer containing a carboxyl group as described above.
[0034] The alkali-soluble polymer (A) can be used alone or in combination of two or more.
[0035] The acid value of the alkali-soluble polymer (A) is preferably 20 to 300 (mgKOH / g), more preferably 40 to 250 (mgKOH / g), and particularly preferably 50 to 200 (mgKOH / g). By setting the acid value of the alkali-soluble polymer (A) within such range, it becomes easy to obtain a cured product that is excellent in developability, resolution, and reflectance.
[0036] The carboxylic acid equivalent of the alkali-soluble polymer (A) is preferably 100 to 1000 (g / eq), more preferably 200 to 800 (g / eq), and particularly preferably 300 to 500 (g / eq). By setting the carboxylic acid equivalent of the alkali-soluble polymer (A) within such a range, it becomes easy to obtain a cured product that is excellent in developability, resolution, and reflectance.
[0037] The cyclohexyl group equivalent of the alkali-soluble polymer (A) is preferably 100 to 1000 (g / eq), more preferably 200 to 800 (g / eq), and particularly preferably 300 to 600 (g / eq). By setting the cyclohexyl group equivalent of the alkali-soluble polymer (A) within such range, it becomes easier to obtain a cured product having excellent performance in various respects.
[0038] When the alkali-soluble polymer (A) contains a (meth)acryloyl group, the (meth)acrylic equivalent of the alkali-soluble polymer (A) is preferably 100 to 2000 (g / eq), more preferably 200 to 1800 (g / eq), and particularly preferably 300 to 1500 (g / eq). By setting the carboxylic acid equivalent of the alkali-soluble polymer (A) within such a range, it becomes easier to obtain a cured product having excellent performances.
[0039] The weight average molecular weight of the alkali-soluble polymer (A) can be 1,500 to 150,000, preferably 1,500 to 100,000, more preferably 1,500 to 50,000, and particularly preferably 1,500 to 40,000. By setting the weight average molecular weight of the alkali-soluble polymer (A) within such a range, it becomes easier to obtain a cured product having excellent performances.
[0040] The content of the alkali-soluble polymer (A) in the resin composition is preferably 5 mass% or more, 8 mass% or more, or 10 mass% or more, based on the total mass of the solid content of the resin composition excluding the white pigment, and is preferably 50 mass% or less, 45 mass% or less, or 40 mass% or less.
[0041] <<Urethane polymer (B)>> The urethane polymer (B) is, for example, a reaction product between a polyol having two or more hydroxyl groups in one molecule and a polyisocyanate having two or more isocyanate groups in one molecule.
[0042] The urethane polymer (B) may be any known urethane polymer, and is not particularly limited. The urethane polymer (B) is preferably a carboxyl group-containing urethane polymer (hereinafter, referred to as a carboxyl group-containing urethane resin). The carboxyl group-containing urethane resin, which is preferably used as the urethane polymer (B), will be described in detail below.
[0043] The carboxyl group-containing urethane resin is preferably obtained by using a compound having an isocyanate group that is not directly bonded to an aromatic ring. The resin composition contains a carboxyl group-containing urethane resin, and thereby the adhesion to the base and the developability are improved. The carboxyl group-containing urethane resin may be a carboxyl group-containing urethane resin having an ethylenically unsaturated group, or a carboxyl group-containing urethane resin having no ethylenically unsaturated group. Among them, a carboxyl group-containing urethane resin having an ethylenically unsaturated group is preferable because it has excellent photocurability and development resistance.
[0044] Specifically, the carboxyl group-containing urethane resin is preferably a urethane resin having a phenolic hydroxyl group introduced at the end by the reaction of a compound (a) having an isocyanate group not directly bonded to an aromatic ring, a compound (b) having two or more alcoholic hydroxyl groups in one molecule, and a compound (c) having one alcoholic hydroxyl group and one or more phenolic hydroxyl groups in one molecule, which also functions as a reaction terminator. In addition, the urethane resin may include a urethane resin obtained by the reaction of a compound (a) having an isocyanate group not directly bonded to an aromatic ring with a compound (b) having two or more alcoholic hydroxyl groups in one molecule, in which a phenolic hydroxyl group is introduced at the molecular side chain using a compound having a phenolic hydroxyl group and two or more alcoholic hydroxyl groups as the compound (b), or a urethane resin in which a carboxyl group is introduced at the molecular side chain using a compound having a carboxyl group and two or more alcoholic hydroxyl groups in one molecule. In the latter urethane resin, the above-mentioned compound (c) having one alcoholic hydroxyl group and one or more phenolic hydroxyl groups in one molecule can be used as an end-capping agent (reaction terminator). In addition, various conventionally known reaction terminators can be used, such as monohydroxyl compounds such as aliphatic alcohols and monohydroxymono(meth)acrylate compounds, and monocarboxylic acids having functional groups capable of undergoing addition reactions or condensation reactions with isocyanate groups, such as alcoholic hydroxyl groups, amino groups, and thiol groups.
[0045] For example, in the case of the preferred urethane resin, the carboxyl group-containing urethane resin may be prepared by mixing and reacting a compound (a) having an isocyanate group not directly bonded to an aromatic ring, a compound (b) having two or more alcoholic hydroxyl groups in one molecule, and a compound (c) having one alcoholic hydroxyl group in one molecule all at once; alternatively, the compound (a) having an isocyanate group not directly bonded to an aromatic ring may be reacted with a compound (b) having two or more alcoholic hydroxyl groups in one molecule, followed by reaction with the compound (c) having one alcoholic hydroxyl group in one molecule, which also functions as a reaction terminator. In the case of the other urethane resins described above, the compound (a) having an isocyanate group not directly bonded to an aromatic ring, the compound (b) having a phenolic hydroxyl group and / or a carboxyl group and two or more alcoholic hydroxyl groups in one molecule, and a reaction terminator may be mixed together and reacted at once, but from the viewpoint of molecular weight adjustment, the compound (a) having an isocyanate group not directly bonded to an aromatic ring may be reacted with the compound (b), and then the reaction terminator may be reacted.
[0046] The reaction proceeds without a catalyst by stirring and mixing at room temperature to 100° C., but in order to increase the reaction rate, it is preferable to heat to 70 to 100° C. The appropriate reaction ratio (molar ratio) of the above components (a) to (c) is (a):(b)=1:1 to 2:1, preferably 1:1 to 1.5:1, and (a+b):(c)=1:0.01 to 0.5, preferably 1:0.02 to 0.3.
[0047] As the compound (a) having an isocyanate group not directly bonded to an aromatic ring, various known compounds having an isocyanate group not directly bonded to an aromatic ring can be used, and are not limited to a specific compound. Specific examples of the compound (a) having an isocyanate group not directly bonded to an aromatic ring include aliphatic diisocyanates such as hexamethylene diisocyanate, branched aliphatic diisocyanates such as trimethylhexamethylene diisocyanate, isophorone diisocyanate, (o, m, or p)-(hydrogenated) xylene diisocyanate, methylene bis(cyclohexyl isocyanate), cyclohexane-1,3-dimethylene diisocyanate, and cyclohexane-1,4-dimethylene diisocyanate. Among these, hexamethylene diisocyanate, which is an aliphatic diisocyanate, and trimethylhexamethylene diisocyanate, which is a branched aliphatic diisocyanate, are preferred. These compounds having an isocyanate group not directly bonded to an aromatic ring can be used alone or in combination of two or more. When these diisocyanate compounds are used, a cured product having excellent environmental resistance and low warpage can be obtained. In addition, aromatic diisocyanates can also be used within a range that does not impair the effects of the present invention.
[0048] Next, as the compound (b) having two or more alcoholic hydroxyl groups, various polyols known in the art can be used, and are not limited to a specific compound. However, preferred examples of the compound that can be used include polycarbonate polyols such as polycarbonate diol, polyether polyols, polyester polyols, polyolefin polyols, acrylic polyols, polybutadiene polyols, polyisoprene polyols, hydrogenated polybutadiene polyols, hydrogenated isoprene polyols, phosphorus-containing diols, bisphenol A alkylene oxide adduct diols, compounds having a carboxyl group and an alcoholic hydroxyl group, compounds having a phenolic hydroxyl group and an alcoholic hydroxyl group, and phosphorus-containing polyols. Examples of the polycarbonate diol include polycarbonate diol (b-1) containing repeating units derived from one or more linear aliphatic diols as constituent units, polycarbonate diol (b-2) containing repeating units derived from one or more alicyclic diols as constituent units, and polycarbonate diol (b-3) containing repeating units derived from both linear aliphatic diols and alicyclic diols as constituent units. In addition, when a compound (b-4) having a carboxyl group and two or more alcoholic hydroxyl groups, or a compound (b-5) having a phenolic hydroxyl group and two or more alcoholic hydroxyl groups, is used, a functional group (phenolic hydroxyl group or carboxyl group) can be provided on the molecular side chain. When a phosphorus-containing polyol (b-6) is used, flame retardancy can be imparted to the urethane resin. These compounds (b-1) to (b-6) can be used alone or in a mixture of two or more.
[0049] Specific examples of the polycarbonate diol (b-1) containing, as a constituent unit, a repeating unit derived from one or more of the above-mentioned linear aliphatic diols include polycarbonate diols derived from 1,6-hexanediol, polycarbonate diols derived from 1,5-pentanediol and 1,6-hexanediol, polycarbonate diols derived from 1,4-butanediol and 1,6-hexanediol, polycarbonate diols derived from 3-methyl-1,5-pentanediol and 1,6-hexanediol, and polycarbonate diols derived from 1,9-nonanediol and 2-methyl-1,8-octanediol.
[0050] A specific example of the polycarbonate diol (b-2) containing, as a constituent unit, a repeating unit derived from one or more of the above-mentioned alicyclic diols is a polycarbonate diol derived from 1,4-cyclohexanedimethanol.
[0051] A specific example of the polycarbonate diol (b-3) containing repeating units derived from both the linear aliphatic diol and the alicyclic diol as constituent units is a polycarbonate diol derived from 1,6-hexanediol and 1,4-cyclohexanedimethanol.
[0052] Specific examples of the compound (b-4) having a carboxyl group and two or more alcoholic hydroxyl groups include dimethylolpropionic acid, dimethylolbutanoic acid, etc. By using these compounds having a carboxyl group and two or more alcoholic hydroxyl groups, the carboxyl group can be easily introduced into the urethane resin.
[0053] Specific examples of the compound (b-5) having the above-mentioned phenolic hydroxyl group and two or more alcoholic hydroxyl groups include 6-hydroxy-5-methyl-1,3-benzenedimethanol, 2,4-di(hydroxymethyl)-6-cyclohexylphenol, 3,3'-methylenebis(2-hydroxy-5-methyl-benzenemethanol), 4,4'-(1-methylethylidene)bis[2-methyl-6-hydroxymethylphenol], 4,4'-[1,4-phenylenebis(1-methylethylidene)bis[2-methyl-6-hydroxymethylphenol], 1,3-benzenedimethanol, 4,4'-methylenebis(2-methyl-6-hydroxymethylphenol), 4,4'-methylenebis(2,5-dimethyl-3-hydroxymethylphenol), 4,4'-cyclohexylidenebis(2-methyl-6-hydroxymethylphenol), 4,4'-cyclohexylidenebis(2-cyclohexyl-6-hydroxymethylphenol), 2,6-bis[(2-hydroxy-3-hydroxymethyl-5-methylphenyl)methyl]-4-methylphenol, 2-hydroxy -5-ethyl-1,3-benzenedimethanol, 2-hydroxy-4,5-dimethyl-1,3-benzenedimethanol, 2-hydroxy-5-(1-methylpropyl)-1,3-benzenedimethanol, 4-(1,1-dimethylethyl)-2-hydroxy-1,3-benzenedimethanol, 2-hydroxy-5-cyclohexyl-1,3-benzenedimethanol, 2-hydroxy-5-(1,1,3,3-tetramethylbutyl)-1,3-benzenedimethanol, 2,6-bis[(4-hydroxy-3-hydroxymethyl-2,5-dimethylphenyl)methy] [(4-hydroxy-3-hydroxymethyl-2,5-dimethylphenyl)methyl]-4-cyclohexylphenol, 2-hydroxy-1,3,5-benzenetrimethanol, 3,5-dimethyl-2,4,6-trihydroxymethylphenol, 4,4',4"-ethylidinetris(2-methyl-6-hydroxymethylphenol), 2,3,5,6-tetra(hydroxymethyl)-1,4-benzenediol, 4,4'-methylenebis[2,6-bis(hydroxymethyl)phenol], and the like.By using these compounds having a phenolic hydroxyl group and an alcoholic hydroxyl group, the phenolic hydroxyl group can be easily introduced into the urethane resin.
[0054] The polycarbonate diol preferably has a number average molecular weight of 200 to 5,000. When the polycarbonate diol contains repeating units derived from a linear aliphatic diol and an alicyclic diol as constituent units and the copolymerization ratio of the linear aliphatic diol to the alicyclic diol is 3:7 to 7:3 by mass, the polycarbonate diol preferably has a number average molecular weight of 400 to 2,000.
[0055] Examples of the above-mentioned bisphenol A-based alkylene oxide adducts include ethylene oxide adducts, propylene oxide adducts, and butylene oxide adducts of bisphenol A.
[0056] Specific examples of the phosphorus-containing polyol include FC-450 (manufactured by Asahi Denka Kogyo Co., Ltd.), M-Ester (manufactured by Sanko Co., Ltd.), and M-Ester-HP (manufactured by Sanko Co., Ltd.) By using this phosphorus-containing polyol, a phosphorus compound can be introduced into the urethane resin, and flame retardancy can be imparted.
[0057] Next, as the compound (c) having one alcoholic hydroxyl group, various monohydroxy compounds known in the art can be used, and are not limited to specific compounds. Examples of the compound include, but are not limited to, methanol, ethanol, n-propanol, isopropanol, n-butanol, isobutanol, sec-butanol, t-butanol, amyl alcohol, hexyl alcohol, octyl alcohol, 2-hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, hydroxybutyl (meth)acrylate, cyclohexane dimethanol mono(meth)acrylate, caprolactone or alkylene oxide adducts of the above (meth)acrylates, glycerin di(meth)acrylate, trimethylol di(meth)acrylate, pentaerythritol tri(meth)acrylate, dipentaerythritol penta(meth)acrylate, ditrimethylolpropane tri(meth)acrylate, allyl alcohol, allyloxyethanol, glycolic acid, and hydroxypivalic acid.
[0058] The compound (c) having a phenolic hydroxyl group and one alcoholic hydroxyl group per molecule is used for the purpose of introducing a phenolic hydroxyl group into polyurethane, and also functions as a terminal blocking agent for polyurethane. In particular, a compound having one alcoholic hydroxyl group and a phenolic hydroxyl group per molecule that can react with isocyanate functions as a reaction terminator. Specific examples of such a compound (c) include, for example, hydroxymethylphenol, hydroxymethylcresol, hydroxymethyl-di-t-butylphenol, p-hydroxyphenyl-2-methanol, p-hydroxyphenyl-3-propanol, p-hydroxyphenyl-4-butanol, hydroxyethylcresol, 2,6-dimethyl-4-hydroxymethylphenol, 2,4-dimethyl-6-hydroxymethylphenol, 2,3,6-trimethyl-4-hydroxymethylphenol, 2-cyclohexyl-4-hydroxymethyl-5-methylphenol, 4-methyl-6-hydroxymethylbenzene-1,2-diol, 4-(1,1-dimethylphenyl)-2- ...2-methyl-4-hydroxymethylphenol, 2-cyclohexyl-4-hydroxymethyl-2-methyl-4-hydroxymethylphenol, 2-cyclohexyl-4-hydroxymethyl-2-methyl-4-hydroxymethylphenol, 2-cyclohex Examples of the compound (c) include, but are not limited to, hydroxyalkylphenols or hydroxyalkylcresols such as (ethylethyl)-6-hydroxymethylbenzene-1,2-diol, esters of phenols having a carboxyl group-containing substituent such as hydroxybenzoic acid, hydroxyphenylbenzoic acid, or hydroxyphenoxybenzoic acid with ethylene glycol, propylene glycol, diethylene glycol, triethylene glycol, dipropylene glycol, tripropylene glycol, and the like, monoethylene oxide adducts of bisphenols, monopropylene oxide adducts of bisphenols, p-hydroxyphenethyl alcohol, and the like. These compounds (c) can be used alone or in combination of two or more.
[0059] The weight average molecular weight of the carboxyl group-containing urethane resin is preferably 500 to 100,000, more preferably 8,000 to 50,000. Here, the weight average molecular weight is a value measured by gel permeation chromatography in terms of polystyrene. When the weight average molecular weight of the carboxyl group-containing urethane resin is 500 or more, the elongation, flexibility, and strength of the cured film are improved, and when it is less than 100,000, the resin is developable, has improved solubility, and does not become too high in viscosity after dissolution.
[0060] The acid value of the carboxyl group-containing urethane resin is preferably in the range of 10 to 120 mgKOH / g, more preferably 20 to 80 mgKOH / g. When the acid value is 10 mgKOH / g or more, the reactivity with the thermosetting component is improved, and the heat resistance is improved. On the other hand, when the acid value is 120 mgKOH / g or less, the resist properties such as alkali resistance and electrical properties of the cured film are improved. The acid value of the resin is a value measured in accordance with JIS K5601-1-2-1:1999.
[0061] These carboxyl group-containing urethane resins may be used alone or in combination of two or more.
[0062] The urethane polymer (B) may be a urethane resin that does not contain a carboxyl group, which is obtained by synthesizing a urethane resin without using a compound (b-4) having a carboxyl group and two or more alcoholic hydroxyl groups. The urethane polymer (B) may be obtained by using a compound having an isocyanate group directly bonded to an aromatic ring (e.g., tolylene diisocyanate, diphenylmethane diisocyanate, etc.).
[0063] In the synthesis of the urethane polymer (B), when a compound having a reactive group such as a (meth)acryloyl group is used as the compound (c) having one alcoholic hydroxyl group described above, a urethane prepolymer (B) having a reactive group introduced at its terminal can be easily obtained.
[0064] The urethane polymer (B) can be used alone or in combination of two or more.
[0065] When the urethane polymer (B) contains a carboxyl group, the acid value of the urethane polymer (B) is preferably 10 to 300 (mgKOH / g), more preferably 20 to 200 (mgKOH / g), and particularly preferably 30 to 100 (mgKOH / g). By setting the acid value of the urethane polymer (B) within such a range, it becomes easier to obtain a cured product having excellent performance in various respects.
[0066] When the urethane polymer (B) contains a carboxyl group, the carboxylic acid equivalent of the urethane polymer (B) is preferably 100 to 2500 (g / eq), more preferably 200 to 2000 (g / eq), and particularly preferably 500 to 1500 (g / eq). By setting the carboxylic acid equivalent of the urethane polymer (B) within such a range, it becomes easier to obtain a cured product having excellent performance in various respects.
[0067] The weight average molecular weight of the urethane polymer (B) is preferably from 2000 to 150000, more preferably from 3000 to 100000, and particularly preferably from 4000 to 50000. By setting the weight average molecular weight of the urethane polymer (B) within such a range, it becomes easier to obtain a cured product having excellent performance in various respects.
[0068] The content of the urethane polymer (B) in the resin composition is preferably 5 mass% or more, 8 mass% or more, or 10 mass% or more, based on the total mass of the solid content of the resin composition excluding the white pigment, and is preferably 50 mass% or less, 45 mass% or less, or 40 mass% or less.
[0069] Here, the ratio (B / A) of the content of the urethane polymer (B) to the content of the alkali-soluble polymer (A) in the resin composition is preferably 0.1 or more, 0.2 or more, or 0.5 or more, and is preferably 10.0 or less, 5.0 or less, or 4.0 or less.
[0070] The ratio (C / A) of the content of the alkali-soluble polymer (A) to the content of the thiol group-containing compound (C) is preferably 0.10 or more, or 0.20 or more, and is preferably 2.00 or less, 1.50 or less, 1.00 or less, or 0.60 or less.
[0071] The ratio (C / B) of the content of the urethane polymer (B) to the content of the thiol group-containing compound (C) is preferably 0.10 or more, or 0.20 or more, and is preferably 2.00 or less, 1.50 or less, 1.00 or less, or 0.60 or less.
[0072] <<Thiol group-containing compound (C)>> The thiol group-containing compound (C) is a compound having at least one (preferably two or more) thiol groups in one molecule.
[0073] Examples of the thiol group-containing compound (C) include alkylthiol compounds; polyethers having terminal thiol groups; polythioethers having terminal thiol groups; thiol compounds obtained by reacting an epoxy compound with hydrogen sulfide; thiol compounds having terminal thiol groups obtained by reacting a polythiol compound with an epoxy compound; ester compounds of polyols and mercapto organic acids; mercapto-modified (meth)acrylates; and the like.
[0074] Specific examples of the monofunctional thiol group-containing compound (C) include β-mercaptopropionic acid, methyl-3-mercaptopropionate, 2-ethylhexyl-3-mercaptopropionate, n-octyl-3-mercaptopropionate, methoxybutyl-3-mercaptopropionate, and stearyl-3-mercaptopropionate. Specific examples of the polyfunctional thiol group-containing compound (C) include 1,4-butanedithiol, 1,5-pentanedithiol, 1,6-hexaneedithiol, 1,8-octanedithiol, 1,9-nonanedithiol, 1,10-decanedithiol, trimethylolpropane tris(3-mercaptopropionate), pentaerythritol tetrakis(3-mercaptopropionate), tris-[(3-mercaptopropionyloxy)-ethyl] -isocyanurate, tetraethylene glycol bis(3-mercaptopropionate), dipentaerythritol hexakis(3-mercaptopropionate), pentaerythritol tetrakis(3-mercaptobutyrate), 1,3,5-tris(3-mercaptobutyryloxyethyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, 1,4-bis(3-mercaptobutyryloxy)butane, and the like.
[0075] The thiol group-containing compound (C) preferably contains a mercapto-modified (meth)acrylate. The mercapto-modified (meth)acrylate is a compound obtained by reacting a polythiol compound with a polyfunctional (meth)acrylate. Examples of the mercapto-modified (meth)acrylate include those disclosed in JP 2023-097118 A.
[0076] The thiol group-containing compound (C) can be used alone or in combination of two or more.
[0077] The content of the thiol group-containing compound (C) in the resin composition is preferably 2 mass% or more, 5 mass% or more, 10 mass% or more, or 15 mass% or more based on the total mass of the solid content of the resin composition excluding the white pigment, and is preferably 40 mass% or less, 30 mass% or less, or 20 mass% or less.
[0078] <<White pigment (D)>> As the white pigment (D), any conventionally known white pigment can be used.
[0079] Examples of the white pigment (D) include inorganic white pigments such as oxides such as titanium oxide, zinc oxide, aluminum oxide, silicon oxide, and magnesium oxide; sulfides such as zinc sulfide; hydroxides such as lead hydroxide and aluminum hydroxide; sulfates such as barium sulfate; and carbonates such as calcium carbonate. The white pigment may be a coated particle in which the surface of the particle is coated with a white material. The white pigment may be surface-treated to increase the reflectance, etc.
[0080] The white pigment (D) may be used alone or in combination of two or more.
[0081] The white pigment (D) preferably contains titanium oxide.
[0082] The crystal form of titanium oxide is not particularly limited, and may be, for example, rutile titanium oxide or anatase titanium oxide.
[0083] The average particle size of titanium oxide is not particularly limited. The volume average particle size (D50) of titanium oxide is, for example, 100 to 1000 nm, 120 to 500 nm, or 150 to 400 nm.
[0084] When the total of the alkali-soluble polymer (A), the urethane polymer (B), and the thiol group-containing compound (C) is taken as 100 parts by mass, the content of the white pigment (D) (or the content of titanium oxide) is preferably 100 parts by mass or more, 150 parts by mass or more, 200 parts by mass or more, or 250 parts by mass or more, in terms of solid content, and is preferably 600 parts by mass or less, 550 parts by mass or less, 500 parts by mass or less, 450 parts by mass or less, or 400 parts by mass or less. More specifically, the content of the white pigment (D) (or the content of titanium oxide) is preferably 200 to 500 parts by mass, or 250 to 400 parts by mass.
[0085] <<Thermosetting resin ( E )>> Thermosetting resin ( EExamples of the thermosetting resin include known thermosetting resins such as epoxy resins, polyfunctional oxetane compounds, episulfide resins having two or more cyclic ether groups and / or cyclic thioether groups in the molecule, polyisocyanate compounds (or blocked isocyanate compounds) having two or more isocyanate groups (or blocked isocyanate groups) in one molecule, amine resins (or derivatives thereof) such as melamine resins and benzoguanamine resins, bismaleimide, oxazine, cyclocarbonate compounds, and carbodiimide resins.
[0086] Thermosetting resin ( E ) preferably contains an epoxy resin.
[0087] Examples of epoxy resins include bisphenol type epoxy resins (bisphenol A type epoxy resins, bisphenol F type epoxy resins, bisphenol S type epoxy resins, bisphenol E type epoxy resins, bisphenol M type epoxy resins, bisphenol P type epoxy resins, bisphenol Z type epoxy resins, etc.), novolac type epoxy resins (bisphenol A novolac type epoxy resins, phenol novolac type epoxy resins, cresol novolac epoxy resins, etc.), biphenyl type epoxy resins, biphenyl novolac type epoxy resins, biphenyl aralkyl type epoxy resins, aryl alkylene type epoxy resins, tetraphenylol ethane type epoxy resins, Examples of the epoxy resins include naphthalene type epoxy resins, anthracene type epoxy resins, phenoxy type epoxy resins, dicyclopentadiene type epoxy resins, norbornene type epoxy resins, trihydroxyphenylmethane type epoxy resins, hydantoin type epoxy resins, tetraphenylolethane type epoxy resins, brominated epoxy resins, glycidylamine type epoxy resins, alicyclic epoxy resins, diglycidyl phthalate resins, tetraglycidylxylenoylethane resins, glycidyl methacrylate copolymer epoxy resins, copolymer epoxy resins of cyclohexylmaleimide and glycidyl methacrylate, epoxy modified polybutadiene rubber derivatives, and CTBN modified epoxy resins.
[0088] Thermosetting resin (E ) can be used alone or in combination.
[0089] Thermosetting resin in the resin composition ( E The content of (or the epoxy resin content) is preferably 5 mass % or more, 10 mass % or more, or 15 mass % or more, based on the total mass of the solid content of the resin composition excluding the white pigment, and is preferably 40 mass % or less, 30 mass % or less, or 25 mass % or less.
[0090] <<Polymerization initiator (F)>> Examples of the polymerization initiator (F) include a photopolymerization initiator, a thermal polymerization initiator, etc. The polymerization initiator preferably contains a photopolymerization initiator.
[0091] Examples of the photopolymerization initiator include conventionally known compounds such as halogenated hydrocarbon derivatives (for example, compounds having a triazine skeleton, compounds having an oxadiazole skeleton, compounds having a trihalomethyl group, etc.), acylphosphine compounds such as acylphosphine oxides, hexaarylbiimidazoles, oxime compounds such as oxime derivatives, organic peroxides, thio compounds, ketone compounds, aromatic onium salts, ketoxime ethers, aminoacetophenone compounds, hydroxyacetophenones, azo compounds, azide compounds, metallocene compounds, organic boron compounds, and iron arene complexes.
[0092] The polymerization initiator (F) can be used alone or in combination of two or more.
[0093] The content of the polymerization initiator (F) in the resin composition (preferably the content of the photopolymerization initiator) is preferably 5 mass% or more, 10 mass% or more, or 15 mass% or more based on the total mass of the solid content of the resin composition excluding the white pigment, and is preferably 30 mass% or less, 25 mass% or less, or 20 mass% or less.
[0094] <<Other Ingredients (G)>> Examples of other components include additives such as crosslinking agents, crosslinking aids, defoamers, rust inhibitors, catalysts (reaction catalysts for epoxy resins, thermosetting catalysts), antioxidants, leveling agents, inorganic fillers such as silica, sensitizers, adhesion aids, surfactants, plasticizers, flame retardants, cellulose nanofibers, dispersants, and adhesion imparting agents, provided that the effects of the present invention are not impaired.
[0095] The resin composition (G) may also contain an organic solvent as another component. Examples of the organic solvent include ketones such as acetone, methyl ethyl ketone, and cyclohexanone; acetates such as ethyl acetate, butyl acetate, cellosolve acetate, propylene glycol monomethyl ether acetate, and carbitol acetate; cellosolves such as cellosolve and butyl cellosolve; carbitols such as carbitol and butyl carbitol; aromatic hydrocarbons such as toluene and xylene; and other organic solvents such as dimethylformamide and dimethylacetamide.
[0096] The other components (G) may each be used alone or in combination of two or more.
[0097] The total content of other components (G) (excluding organic solvents) in the resin composition can be 1 mass% or more, 5 mass% or more, or 10 mass% or more, based on the total mass of solids excluding the white pigment, and can be 40 mass% or less, 30 mass% or less, or 20 mass% or less.
[0098] In the white solder resist, a white pigment such as titanium oxide may be highly filled in order to achieve a high reflectance. In that case, a large amount of white pigment may be present near the surface of the cured product. In this way, it was found that the presence of a large amount of white pigment on the surface of the cured product may scratch an article (such as a clip or a metal conveyor) that comes into contact with the cured product, and that the cured product may easily leave a contact mark with such an article, which may lead to the generation of defective products. The resistance to the generation of such contact marks is called scratch resistance. According to the resin composition according to the present disclosure, by combining an alkali-soluble polymer (A), a urethane polymer (B), and a thiol group-containing compound (C) as components of a resin composition containing a white pigment (D), the cyclohexyl group derived from the alkali-soluble polymer (A) contributes to hydrophobicity and compatibility between components, and may also have developability. In addition, by using the urethane polymer (B) in combination, flexibility may be imparted to the obtained cured product. In addition, by containing a thiol group-containing compound (C), it may react quickly with other polymerizable components, etc., and may impart curability to the surface of the obtained cured product. In addition, it was found that the white pigment (D) is less likely to be located near the surface of the cured product obtained using the resin composition according to the present disclosure, compared with conventionally known cured products. The reason for this is unclear, but it is believed that the improved photocurability leads to higher development resistance, making it difficult for titanium oxide to be exposed during development, and that the use of a urethane polymer causes swelling development, which tends to leave a film on the titanium oxide surface. Therefore, it is presumed that a resin composition containing an alkali-soluble polymer (A), a urethane polymer (B), and a thiol group-containing compound (C) can obtain a cured product with excellent scratch resistance, low warpage, undercut properties, etc., even when the resin composition contains (especially a high content of) the white pigment (D). In addition, according to the resin composition according to the present disclosure, discoloration during reflow can be suppressed by including such a component. In addition, when the resin composition contains a thermosetting resin ( E) and polymerization initiator (F), the reactivity and curability are enhanced, and it is presumed that the above-mentioned effects are further enhanced. When a cured product is formed using the resin composition according to the present disclosure, it can be handled in the same way as other solder resists. In addition, since there is little effect when the cured product comes into contact with other articles (clips, metal conveyors, etc.) (there is little effect on how the surface having the cured product is arranged), it can be handled in the same way whether the cured product is provided on one side or both sides. In this way, the cured product formed using the resin composition according to the present disclosure is easy to handle, and productivity efficiency can be improved.
[0099] The resin composition according to the present disclosure can be produced, for example, by mixing the respective raw materials simultaneously or in order and appropriately kneading them using a conventionally known means. Furthermore, each raw material may be prepared in advance as a solution or dispersion before mixing.
[0100] <<<Applications / methods of use of resin composition>>> Hereinafter, as applications / methods of using the resin composition, a dry film using the resin composition and a cured product obtained by using the resin composition will be described.
[0101] <<Dry film>> The dry film has a resin layer obtained by applying the resin composition of the present disclosure to at least one surface of a first film (substrate film) and then drying the applied resin composition. The dry film is used by laminating the resin layer to the substrate so as to be in contact with the substrate.
[0102] The dry film can be produced by uniformly applying the resin composition onto the first film by an appropriate method such as a blade coater, lip coater, comma coater, or film coater, and drying to form the above-mentioned resin layer. The dry film is preferably produced by laminating a second film (protective film) onto the resin layer. The first film and the second film may be made of the same film material or different film materials.
[0103] The film materials for the first film and the second film may be any of those known to be used for dry films.
[0104] As the first film, for example, a thermoplastic film such as a polyester film made of polyethylene terephthalate or the like having a thickness of 2 to 150 μm is used.
[0105] The second film may be a polyethylene film, a polypropylene film, or the like, but it is preferable that the adhesive strength with the resin layer is smaller than that of the first film.
[0106] The thickness of the resin layer on the first film is preferably 100 μm or less, and more preferably in the range of 5 to 50 μm.
[0107] <<Cured product>> A cured product can be obtained by using the resin composition according to the present disclosure or a dry film having a resin layer obtained from the resin composition according to the present disclosure. Hereinafter, a method for producing the cured product and uses thereof will be described.
[0108] <Method of manufacturing the cured product> As an example of a method for producing a cured product according to the present disclosure, a method for producing a pattern film that is a cured product of the resin composition according to the present disclosure by applying the resin composition according to the present disclosure to a negative photolithography method while making it into a photosensitive resin composition (a resin composition containing a component having a photosensitive site) will be described below.
[0109] First, in step 1, a resin composition is applied onto a substrate and dried to form a resin layer. When a dry film is used, the resin layer is formed on the substrate by laminating the dry film onto the substrate using a laminator or the like so that the resin layer comes into contact with the substrate. As a method for applying the resin composition onto a substrate, a method that has conventionally been used for applying a resin composition, for example, a method of applying the resin composition using a spin coater, a bar coater, a blade coater, a curtain coater, a screen printing machine, or the like, a method of spray application using a spray coater, or an inkjet method, etc. can be used. In addition, the method of laminating the dry film onto the substrate is preferably carried out under pressure and heat using a vacuum laminator or the like. By using such a vacuum laminator, when a substrate on which a circuit is formed is used, even if the substrate has unevenness on its surface, the dry film adheres closely to the substrate, so that no air bubbles are mixed in, and the filling of recesses on the substrate surface is improved. The pressure condition is preferably about 0.1 to 2.0 MPa, and the heating condition is preferably 40 to 120°C.
[0110] The drying method performed after applying the resin composition may be air drying, heat drying using an oven or a hot plate, vacuum drying, etc. The drying conditions are not particularly limited, but natural drying, air drying, or heat drying may be performed at 60 to 130° C. for 1 to 30 minutes.
[0111] There are no particular limitations on the substrate on which the resin layer is formed, and examples include printed wiring boards and flexible printed wiring boards with circuits already formed using copper or the like, as well as materials such as paper phenol, paper epoxy, glass cloth epoxy, glass polyimide, glass cloth / non-woven cloth epoxy, glass cloth / paper epoxy, synthetic fiber epoxy, copper-clad laminates for high-frequency circuits using fluororesin, polyethylene, polyphenylene ether, polyphenylene oxide, cyanate, etc., including copper-clad laminates of all grades (FR-4, etc.), as well as metal substrates, polyimide films, polyethylene terephthalate films, polyethylene naphthalate (PEN) films, glass substrates, ceramic substrates, wafer plates, etc.
[0112] Next, in step 2, the resin layer formed on the substrate is irradiated (exposed) to light through a photomask having a pattern, or directly in a pattern. When a dry film is used, the first film is peeled off from the dry film after exposure. If the characteristics are not impaired, the first film may be peeled off from the dry film before exposure and the exposed resin layer may be exposed. For exposure, any device that is equipped with a high-pressure mercury lamp, an ultra-high-pressure mercury lamp, a metal halide lamp, a mercury short arc lamp, or the like and irradiates ultraviolet rays in the range of 350 to 450 nm may be used, and further, a direct imaging device (for example, a laser direct imaging device that directly draws an image with a laser according to CAD data from a computer) may also be used. The lamp light source or laser light source of the direct imaging device may have a maximum wavelength in the range of 350 to 450 nm. The exposure amount varies depending on the film thickness, etc., but is generally 10 to 1000 mJ / cm. 2 , preferably 20 to 800 mJ / cm 2 The range may be:
[0113] Next, in step 3, the resin layer after the exposure is treated with a developer. This makes it possible to remove the unexposed parts of the resin layer and form a patterned cured film. After development, the resin layer may be washed with a rinse liquid as necessary.
[0114] The method used for development can be arbitrarily selected from among a dipping method, a shower method, a spray method, a brush method, and the like.
[0115] Examples of the developer include aqueous solutions of inorganic alkalis such as sodium hydroxide, sodium carbonate, sodium silicate, and aqueous ammonia, organic amines such as ethylamine, diethylamine, triethylamine, and triethanolamine, and quaternary ammonium salts such as tetramethylammonium hydroxide and tetrabutylammonium hydroxide. If necessary, an appropriate amount of a water-soluble organic solvent or surfactant such as methanol, ethanol, and isopropyl alcohol may be added to the developer. Thereafter, if necessary, the coating film is washed with a rinse liquid to obtain a pattern film. As the rinse liquid, distilled water, methanol, ethanol, isopropyl alcohol, and the like may be used alone or in combination. The above-mentioned solvents may also be used as the developer.
[0116] In addition, as necessary, in step 4, the patterned cured film may be irradiated with active energy rays and then heat cured, or may be irradiated with active energy rays after heat curing, or may be heat cured only to perform final finish curing (main curing). The heating temperature is not particularly limited, but may be, for example, heating at 100 to 220°C for about 30 to 120 minutes. The atmosphere (gas) used in this step may be air, or an inert gas such as nitrogen or argon.
[0117] <Applications of the cured product> The cured product of the present disclosure can be used for various electronic components including printed wiring boards. The cured product of the present disclosure is preferably used for a light-emitting element mounting substrate because of its excellent reflectance and the low occurrence of defective products.
[0118] Fig. 1 shows an example of a light-emitting element mounting substrate 100 (light-emitting device). More specifically, Fig. 1 shows a conceptual top view of a partial region of the light-emitting element mounting substrate 100. As shown in Fig. 1, the light-emitting element mounting substrate 100 has a substrate 10, a circuit (not shown) provided on the substrate 10, a reflective layer 11 provided so as to cover the circuit, and a plurality of light-emitting elements 12 mounted on the substrate 10.
[0119] The light emitting element 12 is, for example, a light emitting diode.
[0120] The reflective layer 11 is a white solder resist formed by a cured product obtained by using the resin composition according to the present disclosure. The reflective layer 11 protects the circuit and efficiently reflects the light irradiated from the light emitting element 12 to the front surface (upper surface) to enhance the light emitting efficiency. Furthermore, the reflective layer 11 has excellent scratch resistance, and is therefore unlikely to scratch an article that comes into contact with the light emitting element mounting substrate 100. In addition, the reflective layer 11, which is a cured product obtained by using the resin composition according to the present disclosure, has excellent low warpage properties, undercut properties, and the like, and therefore can enhance the reliability of the light emitting element mounting substrate 100.
[0121] 1, the light-emitting element mounting substrate 100 has a plate-like structure, but the light-emitting element mounting substrate 100 may have a structure in which at least a part or the whole is curved or bent, or may be a flexible wiring substrate. In addition, the arrangement of the light-emitting elements 12, such as the density of the light-emitting elements 12 and the distance between the light-emitting elements 12, can be freely changed as appropriate. EXAMPLES
[0122] <<<Preparation of resin composition>>> Resin compositions according to Examples 1-4 and Comparative Examples 1-5 were prepared using the raw materials shown below in the amounts shown in Table 1. Table 1 shows the content (parts by mass) of each raw material calculated as solid content.
[0123] <<Alkali-soluble polymer (A) containing a cyclohexyl group and a carboxyl group>> <a1> An alkali-soluble polymer (A1) containing a cyclohexyl group and a carboxyl group was produced under the following conditions.
[0124] A four-neck flask equipped with a reflux condenser, a thermometer, a glass tube for nitrogen replacement, and a stirrer was charged with 223.8 parts by mass (2.6 mol) of methacrylic acid, 100.1 g (1.0 mol) of methyl methacrylate, 246.7 parts by mass (1.6 mol) of cyclohexyl acrylate, 1400 parts by mass of dipropylene glycol monomethyl ether, and 16.4 parts by mass (0.1 mol) of azobisisobutyronitrile, and the mixture was heated at 75 ° C. for 5 hours under a nitrogen stream to allow the polymerization reaction to proceed. After adding 17.0 parts by mass (0.07 mol) of triphenylphosphine, 156.4 parts by mass (1.1 mol) of glycidyl methyl methacrylate was added, and the mixture was heated at 90 to 100 ° C. for 6 hours to allow the addition of an acryloyl group. Thereafter, triphenylphosphine was deactivated by air bubbling to obtain an alkali-soluble polymer (A1) containing a cyclohexyl group and a carboxyl group (solid acid value: 110 mg KOH / g, solid concentration: 35 mass%, weight average molecular weight Mw: 15,000, acrylic equivalent: about 800, cyclohexyl group equivalent: about 500).
[0125] <<Urethane polymer (B)>> <b1> A urethane polymer (B1) was produced under the following conditions. Into a reaction vessel equipped with a stirrer, a thermometer, and a condenser, 360 g (0.45 mol) of polycarbonate diol (number average molecular weight 800) derived from 1,5-pentanediol and 1,6-hexanediol as a compound having two or more alcoholic hydroxyl groups, 81.4 g (0.55 mol) of dimethylolbutanoic acid, and 22.1 g (0.16 mol) of hydroxyphenylethyl alcohol as a compound having one alcoholic hydroxyl group and one or more phenolic hydroxyl groups in one molecule were charged. Next, 200.9 g (1.08 mol) of trimethylhexamethylene diisocyanate was added as a compound having an isocyanate group not directly bonded to an aromatic ring, and the mixture was heated with stirring. When the temperature reached 60°C, the heating was stopped. When the temperature inside the reaction vessel began to drop, the mixture was heated again and stirring was continued at 80°C. The absorption spectrum of the isocyanate group (2280 cm) was measured by infrared absorption spectroscopy. -1 The reaction was terminated upon confirmation that the .alpha.- methyl ether had disappeared. Next, carbitol acetate was added so that the solid content became 50 wt %, to obtain a carboxyl group-containing urethane polymer (B1). The resulting urethane polymer (B1) had an acid value of 48.8 mg KOH / g of solid content, a carboxylic acid equivalent of 1200, and a weight average molecular weight Mw of 16,000.
[0126] <b2> Urethane Polymer Product name: ART RESIN UN-3320HA (manufactured by Negami Industries)
[0127] <<Thiol group-containing compound (C)>> <c1> Thiol-containing mercapto-modified acrylate Product name: ADDITOL LED 01 (manufactured by Daicel) <c2> Secondary polyfunctional thiol compounds Product name: Karenz MT PE1 (manufactured by Resonac)
[0128] <<White pigment (D)>> <d1> Titanium dioxide Product name: Typaque PFC107 (manufactured by Ishihara Sangyo Kaisha, average particle size D50 = 250 nm)
[0129] <<Thermosetting resin ( E )>> <e1> Biphenyl novolac epoxy resin Product name: NC-3000H-CA75 (manufactured by Nippon Kayaku Co., Ltd.) <e2> Biphenyl-based bifunctional epoxy resin Product name: YX-4000 Chemical Substances (Mitsubishi Chemical)
[0130] <<Polymerization initiator (F)>> <f1> Light coincidence begins Product name: Omnirad TPO H (manufactured by IGM Resins BV) <f2> Oxime Photoinitiator Product name: Irgacure OXE04 (manufactured by BASF Japan)
[0131] <<Other Ingredients (G)>> <g1> Crosslinking Agent EO9 Bis A methacrylate Product name: BPE-900 (manufactured by Shin-Nakamura Chemical Co., Ltd.)
[0132] <<<Evaluation>>> The resin compositions according to the respective Examples and Comparative Examples were evaluated for reflectance, scratch resistance, low warpage, undercut properties, and reflow discoloration properties according to the following evaluation methods. The evaluation results are shown in Table 1.
[0133] <<Substrate preparation conditions>> The substrate was prepared under the following conditions. A copper-clad laminate (ESPANEX (manufactured by Nippon Steel Chemical & Material Co., Ltd.; double-sided product with copper thickness of 12 μm and polyimide thickness of 25 μm)) having a thickness of 50 μm × 150 mm × 100 mm was washed with sulfuric acid and hydrogen peroxide, and each of the resin compositions of Examples 1-4 and Comparative Examples 1-5 was applied to a film thickness of 20 μm using a 100-mesh screen, and dried at 70°C for 30 minutes in a hot air circulation drying oven. Thereafter, an exposure device equipped with a high-pressure mercury lamp (short arc lamp) was used to obtain an integrated exposure dose of 500 mJ / cm. 2 Thereafter, the coating was heated in a hot air circulating drying oven at 150° C. for 60 minutes for complete curing to obtain a test substrate.
[0134] <<Reflectance>> For the test substrates obtained by the above method, the cured surface was measured for the Y value (%) of the XYZ color system at 450 nm using the SCI method (including regular reflection) with a spectrophotometer (CM-2600d, manufactured by Konica Minolta) to obtain the reflectance. (Evaluation Criteria) A (Excellent): Reflectance is 87% or more B (Good): Reflectance is 84% or more but less than 87% C (unacceptable): Reflectance is less than 84%
[0135] <<Scratch resistance>> The likelihood of producing defective products is evaluated based on scratch resistance. A board (double-sided copper-clad flexible board) consisting of a 18μm thick polyimide film measuring 100mm x 100mm with 35μm copper foil attached to both sides was placed on the obtained test board, and a 1kg circular weight (weight) with a diameter of 12mm and a flat bottom was placed on top of that. In this state, the double-sided copper-clad flexible board was pulled parallel for about 10cm in 10 seconds, and the appearance of black marks on the coating film was evaluated according to the following criteria. (Evaluation Criteria) A (Excellent): No contact marks (black streaks) were observed after five or more tests. B (Good): Contact marks (black streaks) appear after 2 to 4 tests. C (Fail): Contact marks (black streaks) appear after one test.
[0136] <<Low warpage>> The obtained test substrate was cut into a size of 50 mm x 50 mm, and placed on a cutting mat at room temperature to measure the total warpage at the four corners. The test was performed with n=5, and the average value was calculated and evaluated according to the following criteria. (Evaluation Criteria) A (Excellent): Warpage is less than 1 mm. B (Good): Warpage is 1 mm or more and less than 4 mm. C (unacceptable): Warpage is 4 mm or more.
[0137] <<Undercutting>> A copper-clad laminate (ESPANEX (manufactured by Nippon Steel Chemical & Material Co., Ltd.; copper thickness 12 μm, polyimide thickness 25 μm, double-sided product)) with a thickness of 50 μm×150 mm×100 mm and a conductor circuit with L / S=20 μm / 20 μm to 100 μm / 100 μm formed every L / S=10 μm / 10 μm was washed with sulfuric acid and hydrogen peroxide, and each of the resin compositions of Examples 1-4 and Comparative Examples 1-5 was applied to a film thickness of 20 μm using a 100-mesh screen plate, and dried at 70° C. for 30 minutes in a hot air circulation drying oven. Thereafter, an exposure device equipped with a high-pressure mercury lamp (short arc lamp) was used to obtain an integrated exposure dose of 500 mJ / cm 2 so that a pattern with L / S=20 μm / 20 μm to 100 μm / 100 μm was formed every L / S=10 μm / 10 μm. 2 Thereafter, the film was heated in a hot air circulating drying oven at 150° C. for 60 minutes for complete curing to obtain a substrate for undercut test. The line width of the obtained substrate for evaluating undercut property was measured at a measurement magnification of 500 times using an optical microscope (DIGITAL MICROSCOPE VHX-6000, manufactured by Keyence Corporation) and evaluated according to the following evaluation criteria. (Evaluation Criteria) A (Excellent): A 50 μm line remains on the undercut test substrate. B (Good): No 50 μm lines remain on the undercut test substrate, but a 60 μm line remains. C (Fail): No 60 μm line remains on the undercut test substrate.
[0138] <<Reflow discoloration>> The obtained test substrates were subjected to reflow treatment 1 to 5 times in an air atmosphere at a peak temperature of 260° C. for 60 seconds using a reflow device (NIS-20-82S manufactured by Atec Techtron), and then visually evaluated for discoloration. (Evaluation Criteria) A (Excellent): No discoloration after 5 reflows. B (Good): No discoloration after 3 reflows, but discoloration after 4 reflows. C (Not acceptable): Discoloration occurs after 1 to 3 reflows.
[0139] [Table 1] [Industrial Applicability]
[0140] The resin composition of the present invention makes it possible to produce a white solder resist (cured product) that has high reflectance and is less likely to produce defective products, and can be used for various electronic components. [Explanation of symbols]
[0141] 10 Substrate 11 Reflective layer 12 Light emitting element 100 Light emitting element mounting board
Claims
1. An alkali-soluble polymer (A) containing a cyclohexyl group and a carboxyl group and having an ethylenically unsaturated group; A urethane polymer (B), A compound (C) containing a thiol group; White pigment (D); Contains The resin composition has a content of the white pigment (D) of 100 to 600 parts by mass, calculated as a solid content, when the total amount of the alkali-soluble polymer (A), the urethane polymer (B), and the compound (C) is 100 parts by mass.
2. The resin composition according to claim 1 , wherein the white pigment (D) contains titanium oxide.
3. The resin composition according to claim 1 , wherein the urethane polymer (B) contains a carboxyl group.
4. 3. The resin composition according to claim 1, wherein the content of the white pigment (D) is 200 to 500 parts by mass, calculated as a solid content, when the total amount of the alkali-soluble polymer (A), the urethane polymer (B), and the compound (C) is 100 parts by mass.
5. The resin composition according to claim 1 or 2, further comprising a polymerization initiator.
6. A dry film obtained by applying the resin composition according to claim 1 to a first film.
7. A cured product obtained by using the resin composition according to claim 1 or the dry film according to claim 6.
8. A light-emitting element-mounting substrate comprising the cured product according to claim 7 .
Citation Information
Patent Citations
Inter-layer adhesive film for multilayered printed wiring board and multilayered printed wiring board using the same
JP1999087927A
Photocurable resin composition, dry film, cured article, and printed wiring board
JP2011164270A
Flame retardant thermosetting resin composition, cured product of the same, and printed wiring board using the same
JP2012219232A
Polyurethane resin, method for producing polyurethane resin and resin composition
JP2016089172A
Curable resin composition, dry film, cured product and electronic component
JP2021138916A